For-profit philanthropy : elite power and the threat of limited liability companies, donor-advised funds, and strategic corporate giving - Reiser, Dana Brakman; Dean, Steven A. (New York, NY : Oxford University Press, 2023)
Elite philanthropy has produced countless essential features of modern life. Today, for-profit philanthropic innovations like donor-advised funds threaten its future. In 'For-Profit Philanthropy', Dana Brakman Reiser and Steven A. Dean reveal that philanthropy law has operated as strategic compromise, binding ordinary Americans and elites together in a common purpose. The authors start with an overview of the size and role of the philanthropic sector in the United States and then discuss changes in the regulatory environment that has facilitated new forms of philanthropic organizations.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 2, 2023).
Keywords: Charitable uses, trusts, and foundations -- United States; Charitable uses, trusts, and foundations -- Taxation -- United States; Charitable uses, trusts, and foundations -- Moral and ethical aspects -- United States; Law; Laws of specific jurisdictions & specific areas of law